A regenerated lithium iron phosphate composite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611251759.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]间接再生需通过酸浸、碱浸等步骤将LFP中的锂、铁、磷元素分离提纯,再重新合成LFP正极材料,该工艺流程冗长、酸碱消耗量大、产生大量高盐废水,环保压力大且生产成本偏高,难以实现规模化绿色生产
(1)将工业副产物和废旧磷酸铁锂电池组合使用,不仅降低再生成本,实现工业副产物高值化利用,还能协同发展制糖与锂电回收产业,社会与经济效益显著;
Smart Images

Figure CN122992211A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery material recycling, and in particular to a recycled lithium iron phosphate composite material, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy vehicles and energy storage industries, lithium iron phosphate (LiFePO4) has become increasingly important. Lithium-ion batteries (LFPs), as cathode materials with high safety, long cycle life, and low cost, have been widely used in power batteries and energy storage batteries. Industry data shows that the global volume of retired LFP power batteries has been surging year by year, and is expected to exceed 1 million tons by 2026. The recycling of waste LFPs has become a key link in ensuring lithium resource security and realizing a circular economy, as well as an important way to reduce the cost of the lithium battery industry and reduce environmental pollution. Currently, waste LFP recycling technologies are mainly divided into two categories: indirect recycling and direct recycling.
[0003] Indirect regeneration requires separating and purifying lithium, iron, and phosphorus elements in LFP through acid leaching, alkali leaching, and other steps, and then resynthesizing LFP cathode materials. This process is lengthy, consumes a lot of acid and alkali, generates a large amount of high-salt wastewater, puts great pressure on environmental protection, and has high production costs, making it difficult to achieve large-scale green production.
[0004] Direct recycling technology has become the industry mainstream due to its short process, low energy consumption, and environmental friendliness. Its core principle is to repair LFP lattice defects through lithium replenishment and improve material conductivity through carbon coating, thereby compensating for lithium loss during the recycling process of waste LFP. Issues such as oxidation and decreased conductivity exist, but in direct regeneration technology, the lithium replenishment and carbon coating stages require the use of pure lithium salts and pure carbon sources, respectively; these pure carbon sources are costly, accounting for more than 30% of the cost of regenerated raw materials; the lithium source used for lithium replenishment is... Slightly soluble lithium salts such as LiOH require high-temperature ball milling to achieve uniform mixing with waste LFP, which can easily lead to uneven lithium distribution and insufficient lithium replenishment, thus affecting the electrochemical performance of recycled materials.
[0005] Because the degree of waste of recycled lithium iron phosphate varies, in order to avoid problems such as poor process synergy, most LFP regeneration processes involve reacting the leaching residue from the acid leaching of cathode powder with raw materials such as pure carbon source and lithium source (e.g., CN119833806A). However, this regeneration method is not only expensive in terms of raw material cost, but also requires the use of pure carbon source (such as glucose). The carbon source only undertakes the coating function, and the lithium source only undertakes the lithium replenishment function. The two work independently and lack synergy. Moreover, the process steps are relatively complicated and the energy consumption is high, which is not conducive to large-scale industrial production.
[0006] To overcome the aforementioned problems, a cost-effective and efficient combination of carbon and lithium sources is needed in this field. Crystallized glucose mother liquor is a major byproduct generated during the production of crystalline glucose in the sugar industry, with a huge output, accounting for approximately 25%–30% of the total crystalline glucose production. This mother liquor is rich in glucose (60%–85%), oligosaccharides, and impurities, possessing good reducing properties and carbon source potential. However, currently, a portion of the mother liquor is mainly used in low-value-added fields such as fermentation for alcohol production and feed additives, while another portion is directly discharged or stockpiled due to the difficulty of treatment and high environmental costs, resulting in both resource waste and environmental pollution. Although the glucose in this mother liquor has good reducing properties and carbon source potential, its utilization rate as an industrial byproduct is low, and its complex composition and high impurity content would severely affect product performance if used directly in material synthesis. Therefore, there are no reports of its direct use in the LFP regeneration field.
[0007] Therefore, there is an urgent need to develop a low-cost, green, efficient, and highly synergistic integrated lithium replenishment-carbon coating technology to achieve the dual goals of waste LFP regeneration and glucose mother liquor resource utilization. Summary of the Invention
[0008] To address the technical problems existing in the background art, the present invention proposes a method for preparing a recycled lithium iron phosphate composite material. The preparation method includes: mixing pretreated lithium iron phosphate cathode powder, crystalline glucose mother liquor, soluble lithium salt and water into a slurry; drying the slurry to obtain a precursor powder; and then heat-treating the precursor powder in an inert atmosphere to obtain the recycled lithium iron phosphate composite material.
[0009] The crystalline glucose mother liquor of this invention is an industrial byproduct that urgently needs to be treated. By using this mother liquor as a carbon source, the raw material cost can be reduced by 30%–50%, which can significantly reduce the raw material cost. At the same time, it solves the environmental problems caused by the discharge of glucose mother liquor, realizes "turning waste into treasure", fits the concept of circular economy development, and also promotes the coordinated development of the sugar industry and the lithium battery recycling industry.
[0010] In this invention, when the raw materials are mixed into a slurry, continuous stirring is required. The stirring speed is 300-800 r / min, and the stirring time is 10-480 min (preferably 30-240 min) to ensure complete dissolution of the soluble lithium salt and uniform mixing of the mother liquor and waste LFP. This avoids problems such as uneven lithium distribution and carbon source agglomeration, ensuring the Li... + The carbon source precursor is uniformly attached to the surface of LFP particles.
[0011] Preferably, the pretreatment includes: calcining the cathode powder obtained from the pretreatment of waste lithium iron phosphate batteries in an oxygen-containing atmosphere, crushing and sieving the oxygen-containing calcination product to obtain the pretreated lithium iron phosphate cathode powder; More preferably, the calcination temperature is 450-600℃, and the calcination time is 1-10h; More preferably, the mesh size of the sieve used for screening is 150-400 mesh; In this invention, the pretreatment step can remove impurities, ensure the effectiveness of subsequent lithium replenishment and carbon coating, and avoid residual binder affecting the performance of recycled materials.
[0012] Preferably, the molar ratio of each element in the pretreated lithium iron phosphate cathode powder is Li:Fe:P = 0.7-0.95:1:1.
[0013] Preferably, the solid content of the crystalline glucose mother liquor is 30wt%–70wt%, the glucose content on a dry basis is 60%–85%, the oligosaccharide content is 10%–25%, and the impurity (ash, protein, pigment) content is ≤5%. In this invention, during the recycling process, a portion of the spent lithium iron phosphate batteries... It will be oxidized to This leads to lattice distortion and capacity decay. Crystallized glucose mother liquor, as a carbon-coated precursor, and... The reducing agent, rich in glucose and oligosaccharides, has strong reducing properties. During high-temperature sintering, it can pyrolyze to form a uniform amorphous carbon layer, which can remove the carbon generated in waste LFP due to cyclic aging. Restore to This process repairs lattice distortion, stabilizes the olivine structure of LFP, and improves the capacity and cycle stability of recycled materials. Simultaneously, glucose and oligosaccharides in the glucose mother liquor undergo pyrolysis under a high-temperature inert atmosphere to form an amorphous carbon layer that uniformly coats the surface of LFP particles. This carbon layer can improve the electronic conductivity of LFP, reduce lithium-ion diffusion resistance, and inhibit LFP particle agglomeration, reducing particle pulverization during the cycle and further improving the cycle life of recycled materials; that is, it achieves the synergistic effect of reduction and carbon coating.
[0014] In this invention, the glucose mother liquor is derived from industrial byproducts with different crystallization times, and its concentration varies. It can treat waste lithium iron phosphate batteries with different aging degrees, has strong adaptability, and has a wide range of applications. However, lithium iron phosphate cathode powder with a lower aging degree, such as waste lithium iron phosphate batteries, has a higher adaptability to this process because its crystal lattice is relatively well preserved.
[0015] In this invention, the unique impurities in the crystalline glucose mother liquor are modified by in-situ multi-element doping, giving the regenerated material electrochemical performance superior to that of a pure carbon source system. Impurities such as oligosaccharides, trace organic acids, and trace metal ions (potassium and sodium) remaining in the mother liquor do not produce harmful byproducts during high-temperature pyrolysis; instead, they decompose in-situ to form heteroatom-doped active sites. Trace amounts of oxygen, nitrogen, and metal heteroatoms are successfully introduced into the carbon framework, optimizing the electronic conductivity of the carbon layer and improving the overall conductivity of the material. Simultaneously, the short-chain carbon structure formed by the pyrolysis of oligosaccharides refines the carbon layer grains, constructing a continuous, dense, and porous conductive network, effectively mitigating volume expansion during charging and discharging, repairing minor defects in the lithium iron phosphate lattice, and inhibiting the formation of Li-Fe antisite defects.
[0016] Preferably, the soluble lithium salt is selected from LiCl, LiOAc Lithium formate, lithium citrate, lithium hydroxide , , One or more mixed systems; In this invention, the soluble lithium salt is used as a lithium supplement raw material. The selected lithium salt is water-soluble, has a high lithium content, and is free of harmful impurities. The soluble lithium salt can be flexibly selected as a single or mixed system, and it rapidly ionizes in aqueous solution. , Repairing the surface through lattice diffusion In addition, it can alleviate local defects. Compared with traditional slightly soluble lithium salts, soluble lithium salts do not require high-temperature ball milling and can be uniformly dispersed through liquid phase mixing. This results in higher lithium replenishment efficiency, more uniform distribution, and no introduction of harmful impurities that affect the performance of recycled materials.
[0017] Preferably, the solid-liquid mass ratio of the slurry is 1:2-5.
[0018] Preferably, the dry weight of the crystalline glucose mother liquor is 1-20 wt% of the pretreated waste LFP cathode powder. More preferably, the dry basis weight of the crystalline glucose mother liquor is 5-15 wt% of the pretreated waste LFP cathode powder; Preferably, the Li:Fe molar ratio in the slurry is 1.02-1.08:1.
[0019] In this invention, the above ratio ensures sufficient lithium replenishment without producing excessive lithium residue, while the amount of carbon source can form a continuous and dense carbon layer, improving the conductivity of the material.
[0020] Preferably, the drying process is either spray drying or vacuum drying.
[0021] In this invention, the drying process is to remove moisture from the slurry in preparation for subsequent sintering. When the drying process is spray drying, the operation steps are to introduce the above slurry into a spray dryer (inlet temperature 80-250℃, outlet temperature 50-120℃); when the drying process is vacuum drying, the operation steps are to place the above slurry in a vacuum drying oven (80-120℃, vacuum degree -0.08~-0.1MPa) and dry for 2-6 hours to obtain dried precursor powder.
[0022] Preferably, the inert atmosphere is a nitrogen or argon atmosphere; Preferably, the flow rate of the inert atmosphere is 0.05–10 L / min; Preferably, the heat treatment temperature is 550-800℃, the heat treatment time is 1-8h, and the heat treatment heating rate is 2-40℃ / min, preferably 3-10℃ / min; More preferably, the heat treatment temperature is 600-750℃, and the heat treatment time is 2-5 hours; In this invention, during the heat treatment process, the aforementioned soluble lithium salt ionizes... It has penetrated into the LFP lattice, repairing lithium vacancies; glucose and oligosaccharides in the glucose mother liquor pyrolyze to form an amorphous carbon layer, which coats the surface of LFP particles, while simultaneously reducing... This stabilizes the LFP crystal structure; the heat treatment step is completed simultaneously. Lithium supplementation Reduction and carbon coating simplify the process steps, avoiding the cumbersome process of adding carbon and lithium sources separately and processing them step by step in the traditional process, reducing energy consumption by 20%–30% and improving production efficiency.
[0023] The present invention also proposes a recycled lithium iron phosphate composite material, which is prepared by the above-described preparation method.
[0024] In this invention, the recycled lithium iron phosphate composite material comprises a carbon outer layer and a lithium iron phosphate core. Compared to the dense single carbon layer generated from a high-purity single carbon source, the carbon outer layer formed by the pyrolysis of the mother liquor possesses both a multi-level porous structure and multi-element heteroatom doping characteristics: oxygen, nitrogen, and trace metal heteroatoms are uniformly doped into the carbon framework, optimizing the electronic structure of the carbon layer, significantly improving electronic conductivity, and reducing interfacial contact impedance; at the same time, the short-chain carbon structure formed by the pyrolysis of oligosaccharides can construct a continuous, uniform, and appropriately thick coated carbon film, avoiding the drawbacks of an excessively thick carbon layer hindering lithium ion penetration and an excessively thin carbon layer causing the conductive network to break, while retaining abundant microporous channels, balancing rapid electron conduction and efficient lithium ion migration, and completely solving the technical defects of traditional pure carbon coating layers, such as a single structure, high impedance, and poor adaptability. Lithium iron phosphate core characteristics: Trace amounts of metal heteroatoms in glucose mother liquor can be stably embedded in the interstitial space of the crystal lattice in the high-temperature region, passivating active defects in the crystal lattice, stabilizing the crystal skeleton, and greatly improving the ability of the crystal structure to withstand the stress of lithium insertion and extraction during charging and discharging. This fundamentally suppresses the problems of crystal lattice collapse and structural pulverization during cycling, and ensures the long-term stability and smooth flow of lithium ion insertion and extraction channels.
[0025] The present invention also proposes the application of the above-mentioned recycled lithium iron phosphate composite material in lithium-ion batteries, wherein the composite material is used as the positive electrode active material of lithium-ion batteries.
[0026] In this invention, the 0.1C discharge capacity of the recycled lithium iron phosphate composite material reaches 155-164 mAh / g, and the capacity retention rate after 1000 cycles at 1C is ≥84%, which is close to the performance of virgin LFP materials and superior to products from traditional recycling processes. This material can be directly used in the preparation of positive electrodes for power batteries or energy storage batteries.
[0027] Beneficial effects of this invention: (1) Combining industrial by-products and waste lithium iron phosphate batteries not only reduces recycling costs and realizes high-value utilization of industrial by-products, but also promotes the coordinated development of sugar production and lithium battery recycling industries, resulting in significant social and economic benefits. (2) The three-in-one synergistic effect of lithium replenishment, reduction and carbon coating of the present invention solves the technical pain points of high raw material cost, uneven lithium replenishment and poor process synergy in the prior art; (3) Achieved through liquid phase mixing Uniform distribution ensures more thorough lithium replenishment; the continuous and dense carbon layer formed by the pyrolysis of the mother liquor effectively improves the material's conductivity while simultaneously reducing... Stable lattice; compared to traditional processes, regenerated LFP capacity is increased by 8%–11%, and costs are reduced by 30%–50%; (4) The process is green and environmentally friendly and suitable for large-scale production: the whole process does not produce strong acid, strong alkali, or high-salt wastewater, and the amount of waste discharged is significantly reduced; the process steps are simple and can be connected to the existing LFP regeneration production line. The equipment modification is small and the raw materials are readily available, making it suitable for large-scale industrial promotion and solving the problems of high environmental pressure and high difficulty in scaling up the existing recycling process. Attached Figure Description
[0028] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation
[0029] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0031] The technical solution of the present invention will now be described more clearly and completely with reference to specific embodiments and comparative examples.
[0032] The crystalline glucose mother liquor used in the various embodiments and comparative examples of the present invention is a byproduct of the production of crystalline glucose in the sugar industry. The solid content of the crystalline glucose mother liquor is 30wt%–70wt%, the glucose content on a dry basis is 60%–85%, the oligosaccharide content is 10%–25%, and the impurity (ash, protein, pigment) content is ≤5%.
[0033] Example 1
[0034] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the crystalline glucose mother liquor, soluble lithium salt (LiCl), and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain the stirring speed at 500 r / min and the stirring time at 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace, introduce an inert atmosphere (N2 or Ar, flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3h, and complete the lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0035] Example 2
[0036] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the crystalline glucose mother liquor, soluble lithium salt (LiOAc), and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain a stirring speed of 500 r / min and a stirring time of 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace and introduce an inert atmosphere. Alternatively, use Ar (flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3 hours, and complete lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0037] Example 3
[0038] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the mother liquor of crystallized glucose and soluble lithium salt ( Add the lithium salt and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain a stirring speed of 500 r / min and a stirring time of 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace and introduce an inert atmosphere. Alternatively, use Ar (flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3 hours, and complete lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0039] Example 4
[0040] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the crystalline glucose mother liquor, soluble lithium salt (lithium citrate), and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain a stirring speed of 500 r / min and a stirring time of 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace and introduce an inert atmosphere. Alternatively, use Ar (flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3 hours, and complete lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0041] Example 5
[0042] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the crystalline glucose mother liquor, soluble lithium salt (lithium acetate + lithium hydroxide mixed in proportion) and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain the stirring speed at 500 r / min and the stirring time at 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace and introduce an inert atmosphere. Alternatively, use Ar (flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3 hours, and complete lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0043] Example 6
[0044] This embodiment proposes a recycled lithium iron phosphate composite material, the preparation method of which includes the following steps: (1) Take the LFP positive electrode sheet obtained from the dismantling of retired lithium iron phosphate power battery, place the positive electrode sheet in a muffle furnace, calcine at 500°C for 8 hours in air atmosphere, remove the PVDF binder and original carbon layer on the surface of the electrode sheet, cool to room temperature, crush and sieve (200 mesh) to obtain pretreated LFP positive electrode powder (Li / Fe / P molar ratio of 0.93:1:1) for later use; (2) Add the crystalline glucose mother liquor, soluble lithium salt (lithium formate), and deionized water to a mixing tank and stir until the lithium salt is completely dissolved. Then add the pretreated waste LFP cathode powder. During the feeding process, maintain a stirring speed of 500 r / min and a stirring time of 180 min to form a uniformly dispersed slurry. The standard proportions of each raw material are as follows: The solid-liquid ratio of the slurry is 1:4 (by mass). The Li / Fe molar ratio in the slurry is 1.05:1; The dry weight of the crystalline glucose mother liquor was 10 wt% of the pretreated waste LFP cathode powder. (3) The slurry obtained in step (2) is introduced into a spray dryer (inlet temperature 200℃, outlet temperature 80℃) to obtain dried precursor powder; (4) Place the precursor powder into a tube furnace and introduce an inert atmosphere. Alternatively, use Ar (flow rate 0.05-10 L / min), control the heating rate at 5℃ / min, heat to 650℃, hold for 3 hours, and complete lithium replenishment. The reduction and carbon coating reactions are integrated. (5) After sintering, the product is naturally cooled to room temperature, crushed and sieved (200-400 mesh) to obtain recycled lithium iron phosphate composite material.
[0045] Comparative Example 1 This comparative example proposes a recycled lithium iron phosphate composite material, which is prepared in the same way as in Example 1, except that the “crystallized glucose mother liquor” in step (2) is replaced with “glucose aqueous solution”.
[0046] Comparative Example 2 The lithium iron phosphate material used in this comparative example is commercially available virgin lithium iron phosphate material.
[0047] Battery fabrication and testing steps: Regenerated lithium iron phosphate composite materials from each example and comparative example were taken and dispersed in N-methylpyrrolidone (NMP) solvent at a ratio of 96:1.5:2.5 to obtain a positive electrode active material layer slurry. The positive electrode active material layer slurry was coated on the surface of the positive electrode current collector aluminum foil, the solvent was dried and rolled to obtain a positive electrode sheet. The prepared positive electrode sheet was assembled with a negative electrode sheet, a separator and an electrolyte to obtain a test battery. Examples 1-6 are designated as P1-P6, and comparative examples 1-2 are designated as dP1-dP2. The 0.1C discharge capacity, 1C cycle 200 times and 1000 cycles capacity retention rate of the test battery were tested. The test methods are as follows, and the test results are shown in Table 1. Test method: 0.1C discharge capacity: At 25℃, each test battery was charged to 3.65V at a constant current of 0.1C, then charged to 0.05C at a constant voltage, and then discharged to 2.5V at a constant current of 0.1C to obtain the discharge capacity at 25℃. Capacity retention rate after 200 and 1000 cycles at 1C: At 25°C, each test battery was first discharged to 2.0V at 1C and then cycled. It was first charged to 3.75V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged to 2.0V at 1C constant current. This charge / discharge cycle was repeated, and the capacity retention rate of the lithium-ion battery after 200 and 1000 cycles at 25°C was calculated.
[0048] Table 1. Performance test results of batteries P1-P6 and dP1
[0049] As shown in Table 1, the recycled lithium iron phosphate composite material of this invention has performance close to that of virgin LFP material and is superior to products from traditional recycling processes.
[0050] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a recycled lithium iron phosphate composite material, characterized in that, The preparation method includes: mixing pretreated lithium iron phosphate cathode powder, crystalline glucose mother liquor, soluble lithium salt and water into a slurry, drying the slurry to obtain precursor powder, and then heat-treating the precursor powder in an inert atmosphere to obtain the regenerated lithium iron phosphate composite material.
2. The method for preparing the recycled lithium iron phosphate composite material according to claim 1, characterized in that, The pretreatment includes: calcining the cathode powder obtained from the pretreatment of waste lithium iron phosphate batteries in an oxygen-containing atmosphere, crushing and sieving the oxygen-containing calcination product, and obtaining the pretreated lithium iron phosphate cathode powder.
3. The method for preparing the recycled lithium iron phosphate composite material according to claim 1 or 2, characterized in that, The molar ratio of each element in the pretreated lithium iron phosphate cathode powder is Li:Fe:P = 0.7-0.95:1:
1.
4. The method for preparing the recycled lithium iron phosphate composite material according to any one of claims 1-3, characterized in that, The solid-liquid mass ratio of the slurry is 1:2-5.
5. The method for preparing the recycled lithium iron phosphate composite material according to any one of claims 1-4, characterized in that, The dry weight of the crystalline glucose mother liquor is 1-20 wt% of the pretreated waste LFP cathode powder.
6. The method for preparing the recycled lithium iron phosphate composite material according to any one of claims 1-5, characterized in that, The Li:Fe molar ratio in the slurry is 1.02-1.08:
1.
7. The method for preparing the recycled lithium iron phosphate composite material according to any one of claims 1-6, characterized in that, The drying process is either spray drying or vacuum drying.
8. The method for preparing the recycled lithium iron phosphate composite material according to any one of claims 1-7, characterized in that, The heat treatment temperature is 550-800℃, the heat treatment time is 1-8h, and the heat treatment heating rate is 2-40℃ / min.
9. A recycled lithium iron phosphate composite material, characterized in that, It is prepared by the method described in any one of claims 1-8.
10. The application of the recycled lithium iron phosphate composite material of claim 9 in a lithium-ion battery, characterized in that, The composite material is used as the positive electrode active material for lithium-ion batteries.
Citation Information
Patent Citations
Waste LFP battery regenerated lithium iron phosphate positive electrode material and preparation and application thereof
CN119833806A